Compatibilization effect of ionic liquid-based surfactants on physicochemical properties of PBS/rice starch blends: an initial study - Shamsuri, Ahmad Adlie; Md. Jamil, Siti Nurul Ain (MDPI, 2020)
Polybutylene succinate (PBS)/rice starch (RS) blends were prepared via the hot-melt extrusion technique through the usage of a twin-screw extruder without and containing ionic liquid-based surfactants (ILbS). Two types of ILbS were used, specifically, 1-dodecyl-3-methylimidazolium trifluoromethanesulfonate, [C12mim][OTf] and 1-dodecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, [C12mim][NTf2] were mixed into the PBS/RS blends at the different contents (0–8 wt.%). The tensile and flexural results showed that the blends containing ILbS have a high tensile extension and tensile energy compared to the blend without ILbS. The blends containing ILbS also have a high flexural extension compared with the blend without ILbS. The blends containing [C12mim][NTf2] have a significant improvement in the tensile energy (up to 239%) and flexural extension (up to 17%) in comparison with the blends containing [C12mim][OTf]. The FTIR spectra demonstrated that the presence of ILbS in the blends generated the intermolecular interactions (ion-dipole force and hydrophobic-hydrophobic interaction) between PBS and RS. The DSC results exhibited that the melting points of the prepared blends are decreased with the addition of ILbS. However, the TGA results showed that the thermal decomposition of the blends containing ILbS are higher than the blend without ILbS. The values of decomposition temperature were 387.4 °C, 381.8 °C, and 378.6 °C of PBS/RS-[C12mim][NTf2], PBS/RS-[C12mim][OTf], and PBS/RS, respectively. In conclusion, the ILbS could significantly improve the physicochemical properties of the PBS/RS blends by acting as a compatibilizer.